MENINGKATKAN PUBLIKASI JURNAL TEOLOGI MELALUI PENGUASAAN BERAGAM METODE PENELITIAN TEOLOGI - Nggebu, Sostenis (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2024)
The problem in this article highlights the importance of increasing the quantity and quality of publication of theological scientific journal articles. The increase is highly determined by researchers who master various scientific research methods in the field of theological studies. The purpose of this article is to discuss mastery of research methods that can support the improvement of the quality and quantity of publication of theological journal articles. The method used is Bible Research. As a result, every researcher in the field of theology must master various methods or approaches in researching biblical texts; adapting the scientific method to research the biblical text; using important points that can support the discovery of principles or teachings that respect the authority of the Bible is the word of God. In conclusion, theological research is very dynamic by adapting scientific methods to increase the publication of theological journals.